2019
DOI: 10.1016/j.ress.2018.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic models for the erosion rate in embankments and reliability analysis of earth dams

Abstract: Probabilistic models for the concentrated leak erosion of earthen water retaining structures are presented. The models predict the values of the critical shear stress, the coefficient of erosion and the pipe radius enlargement, starting from other measurable soil properties and the geometrical dimensions of the embankment. The models account for both the non-cohesive and cohesive contributions to the erosion behavior. A Bayesian approach is used for the treatment of the unknown parameters. An importance sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Focusing the attention in dam engineering field, the most interesting examples aim to determine the model parameters for the risk assessment of earth fill dams [31,32,33,34].…”
Section: Interpretation Of the Dam Structural Behaviour From Monitorimentioning
confidence: 99%
“…Focusing the attention in dam engineering field, the most interesting examples aim to determine the model parameters for the risk assessment of earth fill dams [31,32,33,34].…”
Section: Interpretation Of the Dam Structural Behaviour From Monitorimentioning
confidence: 99%
“…Jin et al (2019) also reported that the GLCP raised the groundwater in their monitoring region, where more than 50% of the shallow soil samples (20 cm depth) suffered from light soil salinization. Equally, if the water in the GLCP does not drain for a long time the land may form a water outlet resulting in an unwanted piping effect, which poses a major threat to the safety of check‐dams (Andreini et al, 2019). In summary, we suggest that the GLCP construction can be strengthened in the arid gully regions to increase the farmland while enhancing soil moisture and relieving water supply pressure.…”
Section: Discussionmentioning
confidence: 99%
“…L(θ|y) is the likelihood function that includes the information from the data vector y. f(θ|y) is the posterior probability distribution that reflects the updated state of information about the model parameter vector θ. κ is a normalizing factor as κ = ( L(θ|y) f (θ)dθ)) −1 . The detailed procedures for Bayesian updates are detailed in other literature [25,32]. Figure 3 shows the main procedure of the proposed method.…”
Section: Proposed Methodsmentioning
confidence: 99%